Implementasi Model Discovery Learning dalam Pembelajaran PPKn untuk Membangun Pemahaman Nilai Demokrasi pada Siswa Sekolah Dasar - Devi, Artika Devi Alamsyah; Fathurrohman (Journal of Contemporary Issues in Primary Education, 2025)
This study aims to analyze the implementation of the Discovery Learning model in Civics Education (PPKn) learning as an effort to develop an understanding of democratic values in elementary school students. The approach used is a literature review by examining various research and relevant books over the past five years. The results of the study indicate that the application of the Discovery Learning model can enhance the understanding of democratic concepts through an active, explorative, and student-centered learning process. This model provides space for students to discover the meaning of democratic values on their own through hands-on learning experiences, group discussions, and reflective activities. Thus, Discovery Learning can be an effective alternative strategy for PPKn learning in fostering early awareness of democracy.